Routes of Thoughts as a innovative proccess en Math Learning - Chiliquinga Campos, Felipe David (2020)
This research has as objective to determine the frequency of use of thinking routines in the teaching - learning process of Mathematics by teachers of the Third Year of the Unified General Baccalaureate of the Fiscal Educational Unit "Arturo Borja" in the school year 2018-2019, with the proposal to suggest a constructivist and innovative methodological procedure, starting from an articulated and technical bibliographic analysis whose theoretical foundations allowed the conceptual scaffolding of thought routines with constructivism as a teaching philosophy.